Last glacial temperature reconstructions using coupled isotopic analyses of fossil snails and stalagmites from archaeological caves in Okinawa, Japan - Ryuji Asami (Nature Portfolio, 2021)
Abstract We applied a new geoarchaeological method with two carbonate archives, which are fossil snails from Sakitari Cave and stalagmites from Gyokusen Cave, on Okinawa Island, Japan, to reconstruct surface air temperature changes over the northwestern Pacific since the last glacial period. Oxygen isotope ratios (δ18O) of modern and fossil freshwater snail shells were determined to infer seasonal temperature variations. The observational and analytical data confirm that δ18O values of fluid inclusion waters in the stalagmite can be regarded as those of spring waters at the sites where snails lived. Our results indicate that the annual mean, summer, and winter air temperatures were lower by 6–7 °C at ca. 23 thousand years ago (ka) and 4–5 °C at ca. 16–13 ka than those of the present day. Our reconstruction implies that surface air cooling was possibly two times greater than that of seawater around the Ryukyu Islands during the Last Glacial Maximum, which potentially enhanced the development of the East Asian summer monsoon during the last deglaciation. Considering the potential uncertainties in the temperature estimations, the climatic interpretations of this study are not necessarily definitive due to the limited number of samples. Nevertheless, our new geoarchaeological approach using coupled δ18O determinations of fossil snails and stalagmite fluid inclusion waters will be useful for reconstructing snapshots of seasonally resolved time series of air temperatures during the Quaternary.